Vestibular Dysfunction in DFNB1 deafness - Dodson, Kelley M (2011)
Mutations of GJB2 and GJB6 (connexin-26 and 30) at the DFNB1 locus are the most common cause of autosomal recessive, nonsyndromic deafness. Despite their widespread expression throughout the vestibular system, vestibular dysfunction has not been widely recognized as a commonly associated clinical feature. The observations of vertigo accompanying DFNB1 deafness in several large families prompted our hypothesis that vestibular dysfunction may be an integral, but often overlooked, component of DFNB1 deafness. Our aim was to define the prevalence of vestibular dysfunction in Cases of DFNB1 deafness and Controls with other forms of deafness. We developed and used a survey to assess symptoms of vestibular dysfunction, medical, and family history was distributed to Cases with deafness due to pathogenic GJB2 and/or GJB6 mutations and deaf Controls without DFNB1 deafness. Our results showed: Surveys were returned by 235/515 Cases (46%) with DFNB1 mutations and 121/ 321 Controls (38%) without these mutations. The mean age of Cases (41) was younger than Controls (51; p<0.001). Vestibular dysfunction was reported by 127 (54%) of Cases and was present at significantly higher rates in Cases than in deaf Controls without DFNB1 deafness (p< 0.03). Most (63%) had to lie down in order for vertigo to subside, and 48% reported that vertigo interfered with activities of daily living. Vertigo was reported by significantly more Cases with truncating than non-truncating mutations and was also associated with a family history of dizziness. We conclude that vestibular dysfunction appears to be more common in DFNB1 deafness than previously recognized and affects activities of daily living in many patients.